Magnetic Properties and Growth‐Induced Anisotropy in Yttrium Thulium Iron Garnet Thin Films. (30th July 2021) - Rosenberg, Ethan R.; Litzius, Kai; Shaw, Justin M.; Riley, Grant A.; Beach, Geoffrey S. D.; Nembach, Hans T.; Ross, Caroline A.
Abstract: Rare‐earth iron garnets (REIG) have recently become the materials platform of choice for spintronic studies on ferrimagnetic insulators. However, thus far the materials studied have mainly been REIG with a single rare earth species such as thulium, yttrium, or terbium iron garnets. In this study, magnetometry, ferromagnetic resonance, and magneto‐optical Kerr effect imaging is used to explore the continuous variation of magnetic properties as a function of composition for Y x Tm3− x iron garnet (Y x Tm3− x IG) thin films grown by pulsed laser deposition on gadolinium gallium garnet substrates. It is reported that the tunability of the magnetic anisotropy energy, with full control achieved over the type of anisotropy (from perpendicular, to isotropic, to an in‐plane easy axis) on the same substrate. In addition, a nonmonotonic composition‐dependent anisotropy term is reported, which is ascribed to growth‐induced anisotropy similar to what is reported in garnet thin films grown by liquid‐phase epitaxy. Ferromagnetic resonance shows linear variation of the damping and the g‐factor across the composition range, consistent with prior theoretical work. Domain imaging reveals differences in reversal modes, remanant states, and domain sizes in Y x Tm3− x iron‐garnet thin films as a function of anisotropy. Abstract : In this study, Y‐substituted TmIG (YTmIG) thin films on GGG are grown and their static and dynamic magnetic properties are characterized. Epitaxy is achieved over the entire range of compositions studied, and Y‐substitution enables the tunability of the magnetic anisotropy. A significant composition‐dependent growth‐induced contribution to the anisotropy is also found to operate in YTmIG.